2008
DOI: 10.1007/s00384-008-0557-2
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the perineum following anorectal cancer excision

Abstract: Despite most patients being treated with pre-operative radiotherapy, we have had significant success in obtaining primary healing of the perineal defect after APR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 36 publications
0
24
0
4
Order By: Relevance
“…Mesh was used by Weiwei et al in all five of their reported cases 18 and Petrie et al in 50% of their cases. 11 We experienced minor wound dehiscence in a few cases. This was due to the fact that the flap was exposed to increased pressure and shearing forces from sitting.…”
mentioning
confidence: 95%
“…Mesh was used by Weiwei et al in all five of their reported cases 18 and Petrie et al in 50% of their cases. 11 We experienced minor wound dehiscence in a few cases. This was due to the fact that the flap was exposed to increased pressure and shearing forces from sitting.…”
mentioning
confidence: 95%
“…The final stage of the dissection is division of the anterior muscles of the pelvic floor (Fig. Some units prefer to use a muscle flap [1,9], particularly when the perineum has been irradiated [9]. This results in preservation of the neurovascular bundles and an extralevator specimen (Fig.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Hurst et al reported a perineal reconstruction for a complicated perineal wound following a proctectomy for Crohn’s disease 2 . Petrie et al demonstrated a significant success rate of 18 cases of flap closure following APR; 3 of these were microvascular transfer of the LD 3 . More recently, the same authors reported a further case using an inferior mesenteric artery stump as the donor vessel 4 .…”
Section: Discussionmentioning
confidence: 99%